Case report: Cyclophosphamide pulse therapy for chronic recalcitrant erythema nodosum leprosum - Machado, Gustavo U.; Amparo, Thiago; Bulhões, Flávia; Machado, Paulo R. L. (Frontiers in Medicine, 2023)
Chronic recalcitrant erythema nodosum leprosum (ENL) or type 2 reaction (T2R) is a severe condition found in about 50% of multibacillary leprosy subjects. T2R is associated with important morbidities and may lead to several disabilities, not only due to nerve damage, but also to the prolonged use of corticosteroids, thalidomide or immunosuppressors. We describe here four leprosy patients with chronic recalcitrant ENL treated with cyclophosphamide pulse therapy. All subjects were under prednisone and thalidomide therapy for at least 30 months but presenting inflammatory activity at any attempt to lower doses. Pulse therapy with 1.0 g of cyclophosphamide was used every 4 -6 weeks at a minimum of 3 applications. After pulse therapy, all cases presented total or partial regression of symptoms and we were able to taper thalidomide and prednisone doses, with a better control of ENL avoiding further hospital admissions and disabilities. No side effects were observed, during or after infusion therapy. Cyclophosphamide pulse therapy may be useful and safe to control chronic recalcitrant ENL.Erythema nodosum leprosum (ENL) or type 2 reaction (T2R) is a common and severe immune inflammatory complication of multibacillary leprosy. T2R is associated with increased levels of inflammatory cytokines and chemokines, like TNF and IL-6 among others, not only in cutaneous lesions but also in several internal organs, leading to systemic involvement. ENL is characterized by the presence of subcutaneous acute and painful nodules associated with fever, myalgia, asthenia, arthritis, neuritis, generalized lymphadenopathy, and many other symptoms, sometimes requiring hospitalization (1,2).Chronic recalcitrant ENL is a hard-to-treat condition that impose long term use of corticosteroids, thalidomide or immunosuppressors resulting in significant morbidity and rising the risk of disability in those patients (1,2). Other drugs like pentoxifylline and clofazimine have been used but seems to be effective in less severe cases. More recently, other therapeutic strategies have Formatado: Inglês (Americano) Formatado: Inglês (Americano) Formatado: Inglês (Americano)